Predicting the Response of Shear-critical Reinforced Concrete Beams using Response-2000 and SNI 2847:2013 - Benny Suryanto; R. Morgan; A.L. Han (Institute of Research and Community Outreach - Petra Christian University, 2016)
This study investigates the accuracy of Response-2000 in predicting the response of shear-critical reinforced concrete beams. The experimental data selected was that obtained by Vecchio and Shim in 2004 on twelve reinforced concrete beams which sought to replicate beams originally tested by Bresler and Scordelis in the early 1960s. This study also aims to compare the results obtained to the predictions of SNI 2847:2013. It is demonstrated that Response-2000 is capable of providing accurate predictions of load-deflection responses up to the peak load, but underestimates the ductility of beams that exhibit a mixed flexure-shear failure mode. It is also shown that both methods provide conservative predictions of the shear strength of beams with no shear reinforcement, with the software providing more consistent and reliable predictions of shear strength of beams containing shear reinforcement.